Preparation of Polyvinylpyrrolidinone With Paracetamol as Drug Polymer - Firyal M.A. AL-Salami; Abbas N.M. AL-Sharify; Khudheyer J. K. (College of Pharmacy / Mustansiriyah University, 2012)
The prodrug polymer was prepared according to ring opening of polyvinyl pyrrollidinone with nuecleophilic attack of hydroxyl group of paracetamol. The new colorless drug polymer was formed with 92% conversion percentage with intrinsic viscosity was equal to (0.61dl/g). The drug polymer was characterized and identified by1H-NMR, IR and UV. Spectroscopy. Controlled released rates were studied in acidic and basic medium at 30 0C and 40 0C. Rate of hydrolysis of paracetamolate ester acts as base > acid, and the rate of release, depends on temperature and pH values. The results show higher hydrolysis at higher temperature as well as higher pH value.